The Future of Islamic Education: Breaking Through Boundaries with Line Follower Robot Trainers Toward the Era of Society 5.0 - Moh Zainul Falah; Wahyu Tri Handoko; Abdullah Iskandar Syah; Farah Wardatul Afifah; Satrio Dwi Sanjaya (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
This research aims to identify and implement the Line Follower Robot Trainer as an innovative effort to advance Islamic education in facing the Society 5.0 era. The research focuses on SMK NU 1 Karanggeneng, Lamongan, as a case study, where robotic technology is used as a learning tool to integrate Islamic concepts with technological advances. This research proposes the Research and Development (R&D). The results showed that using the Line Follower Robot Trainer significantly improved students' understanding of their technological skills. The survey showed that most students (85%) felt more engaged and excited about learning Islam with the help of the Line Follower Robot Trainer. Students reported higher levels of engagement in learning with the robot, and teachers expressed positive support for using this technology in learning. These positive results reflect the potential of technology in enriching students' experiences in preparing for changes in the evolving Society 5.0 era. This research provides a greater understanding of the role of technology in supporting Islamic education, bridging the gap between tradition and innovation, and bringing Islamic education into an increasingly digitized future. The implications of this research can help Islamic education institutions utilize technology as a powerful tool to spread religious values and prepare students to face an increasingly digitally connected era.